Newton H. Chittenden papers - Chittenden, Newton H.
Field notes of the Pacific Coast exploration. Also, manuscript of "Stories Upon the Rocks.
Explorer and author.
Keywords: Pacific Coast (North America) -- Discovery and exploration; Authors; Explorers